EVALUATING THE DEPOSITION OF POLLUTANTS IN THE PORES OF GRANULAR MEDIA DEEP-BED FILTERS - Ekenta, Obi Emmanuel (European Scientific Journal, ESJ, 2015)
This paper focuses on a study related to the rate of removal of pollutants (suspended solids or particulates) from granular media deep-bed (depth) filters designed and constructed for the production of potable water. An approach was developed for computation of quantities of solids deposited in the pores of granular media filters. The continuity equation was applied in assessing the deposition (accumulation) of pollutants within the interstices of mono and dual-media filtration beds in space and time. Normalized turbidity removal-ratio curves were developed for the dual-media and mono-media filters using data from pilot filters that exhibited high efficiency. The results of the study indicate that deposit morphology decreases with media depth and increases with time. The total quantities of material obtained from the summation of deposits in individual layers are substantially equal for the dual and mono-media filters up to the end of filter run time (14 hours) for the mono-media sand filter. The results and findings from this study will be useful to designers and managers of water treatment works in developing and developed countries.